Organoleptic Characteristics of Soy Milk Powder with the Addition of Red Ginger Extract (Zingiber officinale var. rubrum) - Pagune, Jufrin; Nabila, Riska (MultiTech Publisher, 2023)
Soy milk powder is one of the natural products used to diversify liquid soy milk. One of the drawbacks of processed soy milk is its bland taste or odor, which necessitates the addition of essence in the form of red ginger extract. The objective of this research is to determine the best treatment based on organoleptic characteristics, specifically using the hedonic method or panelist preference test. This research employed a completely randomized design (CRD) with 4 treatments, each replicated 3 times: S0 = 500 ml soybean juice, S1 = 500 ml soybean juice + 20 ml red ginger extract, S2 = 500 ml soybean juice + 30 ml, and S3 = 500 ml soybean juice + 40 ml. The organoleptic test results for soy milk powder revealed that the aroma preferred most by the panelists was found in treatment S3 with a score of (3.9), the taste preferred most by the panelists was also found in treatment S3 with a score of (4.4), and the color preferred most by the panelists was found in treatment S0 with a score of (4.1).